KEBIJAKAN DANA DESA: EVALUASI PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT - Firman, Firman; Rahmawati, Restu; Mandela, Muhammad Fathan (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2020)
This research is related to the implementation of central government assistance to villages, in Indonesia, since 2014 it has changed the village government system with significant assistance in development and empowerment in villages. This article examines the extent of the impact of development regulations and empowerment after the regulation of assistance from the central government to be managed by village governments. The method used in this study is to conduct in-depth interviews with village governments who are involved in village development and empowerment. The results of this study indicate that the use of Village funds in Dukuh Picung Village in 2018 is more focused on the development and empowerment sectors. Various implementations in the Village Law regulations cannot be carried out by villages. The development that occurs does not represent the wishes of the wider community because of the lack of responsiveness of the Village apparatus, there are still development and empowerment works that do not pay attention to the aspects of the stipulated regulations. The inadequate use of Village funds in Dukuh Picung Village is caused by several factors, such as the low quality of human resources. Village officials in Dukuh Picung and low sources of funds for empowerment as well as lack of village transparency in making decisions that many neglect the Village Development Plan Deliberation.